Assistance in the Preparation of Work Programs for Intra-Madrasah Student Organization through Basic Student Leadership Training at Madrasah Aliyah Al-Anwar Cangkringrandu Perak Jombang - Sutrisno; Ali Audah; Hasan Abidin; Choirul Anam; Muhamad Taufiq Firmansyah (LP3M STAI At-Tahdzib Jombang, 2026)
Intra-Madrasah Student Organization (Organisasi Siswa Intra Madrasah/OSIM) is a strategic instrument in developing student leadership and character in the madrasah environment. OSIM's effectiveness is hampered by the limited capacity of administrators to develop systematic and contextual work programs. This Community Service (Pengabdian Kepada Masyarakat/PKM) activity aims to improve the leadership and managerial competencies of OSIM administrators at Madrasah Aliyah (MA) Al-Anwar Cangkringrandu Perak Jombang. The activity was carried out by mentoring the preparation of work programs integrated with Basic Student Leadership Training (Latihan Dasar Kepemimpinan Siswa/LDKS) activities. A participatory-educational approach was applied by actively involving OSIM administrators in the process of needs analysis, vision-mission formulation, activity planning, and the preparation of evaluation indicators. The results of the mentoring showed a significant increase in the conceptual understanding of student leadership and the technical ability to develop work programs that are structured, realistic, and oriented to the needs of the madrasah. The resulting work program has gone through a process of presentation and joint reflection, receiving a positive response from OSIM supervisors and the madrasah. This activity proves that the integration between leadership value development and organizational technical mentoring can optimize OSIM's role as a student leadership laboratory, and support the creation of sustainable student organization governance in the madrasah.